Probing Polymer Contact Electrification by Gamma-Ray Radiation - Zhang, Dong Li; Shi, Jian Min; Wang, Zhong Lin; Tang, Wei (Frontiers in Materials, 2022)
Triboelectric Nanogenerators (TENGs) have been regarded as an effective method to solve the energy problem since they were first demonstrated in 2012. Due to their high-power generation and low cost, TENGs have been widely applied in the fields of energy, security, biomedicine, the environment, and so on. For now, many researchers are focusing on contact electrification (CE) and surface modification in order to discover the fundamental CE mechanism and approaches to further enhance the performance of TENG devices. In this work, we employ gamma radiation (γ ray) to induce surface modifications on the dielectric materials (polymers in this work) and study its influence on CE. It is found that, due to the high energy of γ ray, some chemical bonds in polymers are destroyed and reformed. This changes the electron density of the polymer molecule, and thus varies the electron transfer ability of the dielectric materials. Afterward, polytetrafluoroethylene (PTFE) and polyvinyl chloride (PVC) become more negative, and polyethylene terephthalate (PET) become the opposite. Kapton, in particular, remains stable even after 1 MGy-dose radiation. This study reconfirms that electron transfer is the dominant process for polymers-related CE. It also suggests that triboelectric nanogenerators could be fabricated with materials possessing a high anti-radiation ability, and used for sensing or energy generation in space or other environments where radiation exists.